Higher Alcohol Preference Is Not Necessarily Linked to Higher Consumption of Palatable Food in Rats - Sabrina Pham; Sunil Sirohi (Biology and Life Sciences Forum)
Alcohol use disorder (AUD) is a chronic relapsing disorder afflicting millions of people worldwide. Malnutrition is frequently associated with AUD, which could be the result of reduced nutritional intake and impairment in the absorption/metabolism of nutrients because of excessive alcohol drinking. Interestingly, the higher consumption of high calorie/palatable foods is reported in recovering alcoholics who stayed sober. However, it is unclear if the higher calorie or rewarding properties of these palatable foods accounted for the protective effect in these conditions. In the present study, we evaluated the palatable food intake in male and female alcohol-preferring (P-rats) and compared it to alcohol-non-preferring rats (NP-rats). Importantly, alcohol-preferring (P-rats) were selectively bred for a higher alcohol preference and are regarded as a well-characterized model of alcoholism. A group of P- and NP-rats received a high-fat diet (40% fat) on four separate days over a two-week period, and their 24 h caloric intake and change in body weight were recorded. Standard chow and water were available unrestricted to all groups for the entire duration of the study. Total caloric intake in both P- and NP-rats was significantly increased on HFD access days compared to chow-only days, an effect observed in both males and females. Further analysis revealed that the total caloric intake in the P-rats was significantly lower compared to the NP-rats, an effect more significant and pronounced in the female group of rats. Furthermore, body weight increase during this period was significantly lower in the P-rats than the NP-rats, an effect more significant and pronounced in the male group of rats. These data not only document the important differences in the palatable diet intake between alcohol-preferring and non-preferring rats and the sex differences but also highlight that a higher alcohol preference does not necessarily equate to a higher intake of high calorie/palatable food.